(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Tourism finds enormous application of ICT in the development of strategic and operational goals. ICT promises long-term benefits and is a leading force in the tourism industry to enhance development and economic growth. The tourism industry in the western world and some developed countries of Asia have applied ICT for more than 30 years, and have gained tremendous benefits. Nepal which is also growing as one of the favorite tourist destinations lacks proper implementation of ICT in this sector. In our study, we examined how ICT can play a vital role in developing the tourism industry of Nepal. This study is exploratory research based on primary data collected from tourists visiting Nepal, supported by information from tour operators, government agencies, NGOs, and INGOs. A framework is devised based on data and information collected and finally, discussions elaborate on the informational needs, technological architecture, and challenges for the implementation of ICT in the tourism industry of Nepal.